2016
DOI: 10.12913/22998624/62703
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Based Trust Management System for Cloud Environment

Abstract: Cloud computing is a business model with high degree of flexibility, scalability in providing infrastructure, platform and software as a service over the internet. Cloud promises for easiness and reduced expense to service providers and consumers. However, a lack of trust between these two stakeholders has hindered the universal acceptance of cloud for outsourced services. In this paper, a fuzzy based trust management system is proposed to facilitate cloud consumers in identifying trustworthy providers. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the study by Kumar et al [36], a fuzzy-based trust management system was proposed to facilitate cloud service delivery and identify trusted providers. e proposed system simulation showed that the degree of reliability and trust of the proposed system was higher compared with that of other CSPs.…”
Section: Related Workmentioning
confidence: 99%
“…In the study by Kumar et al [36], a fuzzy-based trust management system was proposed to facilitate cloud service delivery and identify trusted providers. e proposed system simulation showed that the degree of reliability and trust of the proposed system was higher compared with that of other CSPs.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the combination of Mamdani and Sugeno fuzzy inference systems in their study would deem inconsistent and no apparent advantage is elaborated with the use of both. On the other hand, for work in [28], the trust value for each CSP is based on four basic parameters namely security, availability, cost and performance. However, since the metrics are evaluated separately, it cannot be confirmed that the trust values would correctly represent the exact condition of the CSP compared to if these metrics are evaluated together.…”
Section: Trust Evaluation Using Fuzzy Logicmentioning
confidence: 99%
“…To develop an overall measure of trust value of the cloud providers, [30] uses Seguno fuzzy technique to process four criteria; scalability, availability, security, usability. Unlike the works in [27] and [28], study in [30] has evaluated all the metrics together but explanation of how each of the criteria are quantified is lacking in all of the works mentioned above.…”
Section: Trust Evaluation Using Fuzzy Logicmentioning
confidence: 99%
“…Conductive polymer being a popular topic discussion among the researchers since its discovery in late 1970 due to of its unique properties and features. Since then, research activities on conductive polymer has increased rapidly, which is indicated by the large number of research results reported through several publications [1,2]. Polyaniline (PANi) is one of the conductive polymer which received much attention and being developed intensively because of their simple preparation and less costly in production costs when compared with that of other groups [3].…”
Section: Introductionmentioning
confidence: 99%
“…Because of such unique properties, a lot of research and development of conducting polymeric materials based on PANi are directed towards the use of PANi in various applications [4]. There have been some routes in preparation of PANi, a few to mention is a chemical oxidation reaction [1], electrochemical method [5] and vacuum deposition technique [6]. Some improved synthesis methods of PANi have been introduced to improve and increase the properties of PANi like electrical conductivity value, heat resistance, etc.…”
Section: Introductionmentioning
confidence: 99%